Insights into Deactivation and Regeneration of an Industrial Cu/Ni/Cr‐Al2O3 Catalyst During Aldehyde Hydrogenation. Issue 23 (6th October 2016) - Reinsdorf, Arne; Korth, Wolfgang; Jess, Andreas; Terock, Michael; Klasovsky, Florian; Franke, Robert
Abstract: The deactivation of a heterogeneous Cu/Ni/Cr‐Al2 O3 aldehyde hydrogenation catalyst was studied using n ‐nonyl aldehyde as model reactant. The reaction network was experimentally determined in batch experiments at 180 °C and 25 bar with either fresh or spent catalyst and also w/o the presence of the catalyst. Accelerated aging was applied to stress the fresh catalyst under model reaction conditions for characterization and comparison to a spent catalyst from an industrial plant. The catalyst structure and morphology were studied by XRD and TEM/EDX. The carbon residues that strongly adsorb on the catalyst surface during hydrogenation were analyzed by BET, TGA, extraction, and chemical disintegration. The amount of strongly adsorbed heavy hydrocarbons was 10 w % for the spent catalyst, causing a decrease in pore volume by 30 %. Regeneration of the catalyst was successfully conducted via oxidation of the carbon residues. Abstract : Hydrogenation is not just hydrogenation : Novel insight into the hydrogenation of oxo‐aldehyde. The deactivation of commercial hydrogenation catalyst was investigated in detail, showing how aldehyde‐aldol side reactions lead to high molecular compounds that strongly adsorb on the catalyst's inner surface.